Experience of pancreaticodigestive anastomosis performing in pancreaticoduodenectomy - Kutovyi , O.B.; Denysova , K.O. (Medicni Perspektivi, 2022)
The aim of the study was to analyze the short-term and long-term results of pancreaticoduodenectomy (PD) on condition of performing different types of pancreaticodigestive anastomoses. The results of 108 PD of the period from 2008 to 2021 performed in the Department of Surgery N 2 on the basis of the Dnipro Regional Hospital named after І. Mechnikov were analyzed. Pancreatojejunostomy (PJ) was formed in 88 (81.5%) cases, pancreaticogastrostomy (PG) ‒ in 20 (18.5%). Depending on the transverse size of pancreatic isthmus and body, diameter of the pancreatic duct the method of PJ was chosen: telescope-type PJ «end-to-end» (n=26), Wirsung-jejunostomy (n=28), original method (n=34). In the PJ group the dense parenchyma of the pancreas was in 51 (58.0%) cases, soft parenchyma ‒ in 37 (42.0%), and in the PG group the dense gland was observed in 12 (60%) cases, soft ‒ in 8 (40%) patients (p>0,05). The number of the early postoperative complications was 43 (39,8±4,7%), among them there were (15,7±3,5%) patients with severe complications who required additional interventions. Mortality was 6.5±2.4%. The best results for the early postoperative complications were obtained in the groups of PG and original PJ. There were statistically significant differences in the total number of cases of the early postoperative complications between the groups of PG (20.0±8.9%) and telescope-type PJ (50.0±9.8%, p=0.037) and Wirsung-jejunostomy (50.0±9.4%, p=0.034), as well as while comparing the total number of patients with complications in the groups of PG and PJ (44.3±5.3%, p=0.045). There were not any statistically significant differences among the late postoperative complications (p>0.05).